The Middle Pleistocene tunnel valley at Schöningen as a Paleolithic archive. Issue 89 (December 2015) - Lang, Jörg; Böhner, Utz; Polom, Ulrich; Serangeli, Jordi; Winsemann, Jutta
Abstract: Schöningen represents one of the key sites for Lower Paleolithic archaeology in central Europe, where a Middle to Late Pleistocene sedimentary succession, locally up to 45 m thick, has been preserved in an Elsterian tunnel valley. After deglaciation, the tunnel valley remained underfilled and provided the accommodation space for Holsteinian interglacial deposition and also kept the artifact-bearing strata below base level for subsequent erosion. The Holsteinian (MIS 9) succession consists of laterally and vertically stacked lacustrine delta systems, which were controlled by repeated lake-level changes. In the face of changing climatic and environmental conditions the long-lived interglacial lake provided an attractive site for animals and early humans. Artifacts were deposited on the subaerial delta plain and became embedded during lake-level rise. Although the area was considerably affected by erosion and glacitectonic deformation during the subsequent Saalian glaciation, the artifact-bearing Holsteinian strata were preserved in the deeper part of the tunnel valley. Tunnel valleys should be regarded as potential archives for interglacial deposits, which may contain important Paleolithic sites. Tunnel valleys may provide accommodation space and also have a high preservation potential. Interglacial lakes situated within underfilled tunnel valleys represented attractive sites for animals and early human hunter-gatherers.